EFFECT OF WORKLOAD AND ORGANIZATIONAL JUSTICE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION : Case Study On Employees Of Perumda Air Minum Tugu Tirta, Malang - Aris Munandar; Agus Hermawan; Syihabudhin Syihabudhin (International Journal of Economy, Education and Entrepreneurship, 2022)
In cases that can cause an organization to fail, excellent and skilled human resources are needed to anticipate this. Employees who have good performance can help the organization achieve the goals that have been set. This study analyzes workload and organizational justice's direct or indirect effect on employee performance mediated by job satisfaction. This study uses an Explanatory Research approach. The sample in this study amounted to 173 employees from a population of 306 employees with the research location at the Tugu Tirta drinking water company in Malang. The instrument used in data collection is in the form of a questionnaire. The data analysis technique used in this research is path analysis. The results showed that: (1) there was a significant effect of workload on job satisfaction; (2) there is a significant effect of organizational justice on job satisfaction; (3) there is a significant effect of job satisfaction on employee performance; (4) there is a significant effect of workload on employee performance; (5) there is a significant effect of organizational justice on employee performance; (6) there is no significant effect of workload on employee performance through job satisfaction; (7) there is no significant effect of organizational justice on employee performance through job satisfaction